2000
DOI: 10.1542/peds.105.6.1188
|View full text |Cite
|
Sign up to set email alerts
|

Medication Use Among Children With Asthma in East Harlem

Abstract: Daily use of antiinflammatory medication for children with persistent or severe asthma in East Harlem was underused. Differences in access to care may explain some findings; however, reasons for ethnic differences in use remain unclear. Both community interventions and additional provider education are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 26 publications
4
71
0
Order By: Relevance
“…For example, a study by Warman et al 10 that measured antiinflammatory drug use among inner-city children with persistent asthma found that only 39% were receiving daily antiinflammatory treatment. A similar study by Diaz et al 11 found that 39% of children with severe asthma were using antiinflammatory medications. However, it was difficult to derive a reasonably bounded estimate for ICS usage rates because of the heterogeneity of the studies.…”
Section: Discussionmentioning
confidence: 75%
“…For example, a study by Warman et al 10 that measured antiinflammatory drug use among inner-city children with persistent asthma found that only 39% were receiving daily antiinflammatory treatment. A similar study by Diaz et al 11 found that 39% of children with severe asthma were using antiinflammatory medications. However, it was difficult to derive a reasonably bounded estimate for ICS usage rates because of the heterogeneity of the studies.…”
Section: Discussionmentioning
confidence: 75%
“…64 Puerto Ricans are among the racial/ethnic groups most widely affected by asthma in the USA. 24,[65][66][67][68][69][70][71][72][73][74] We hypothesized that specific building-level characteristics-presence of pests and building type and conditions-were associated with levels of indoor allergens.…”
Section: Asthma and Indoor Allergensmentioning
confidence: 99%
“…16 -20 For example, studies have documented that minority children are more frequent users of reliever medications such as short-acting ␤-agonists and not control therapies such as inhaled antiinflammatory medications. [17][18][19][20] In addition, data from the National Health and Nutrition Examination Survey III, a survey of the US population, reported that young, poor, and Spanish-speaking children were at high risk for inadequate asthma therapy. 21 A cross-sectional study of inner-city children who were from Washington, DC, and Baltimore, Maryland, and had at least mild persistent asthma found that these children were high nebulizer users of ␤-agonists but low users of inhaled steroids.…”
mentioning
confidence: 99%